1993
DOI: 10.1111/j.1365-2672.1993.tb02777.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an extracellular amylase from Lactobacillus plantarum strain A6

Abstract: A R A D A AND M. RAIMBAULT. 1993. Extracellular amylase from Lactobacillus plantarum A6 was purified by fractionated precipitation with ammonium sulphate and by anion exchange chromatography. The homogeneity of the purified fraction was tested by polyacrylamide gel electrophoresis and showed multiple amylase forms. A major form had a n estimated molecular weight of 50 kDa. It was identified as an a-amylase, with an optimum pH of 5.5, an optimum temperature of 65°C a n d K,,, value of 2.38 g 1-' with soluble st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 16 publications
2
34
0
3
Order By: Relevance
“…The fold purification and yields were comparable to those reported previously; for example, extracellular α-amylase of Lactobacillus plantarum A6 (50-70%) was purified to 35.6% yield with 19.5-fold purification by 40-80% ammonium sulfate precipitation and diethyl aminoethyl anion exchange chromatography 14 …”
Section: Resultssupporting
confidence: 63%
“…The fold purification and yields were comparable to those reported previously; for example, extracellular α-amylase of Lactobacillus plantarum A6 (50-70%) was purified to 35.6% yield with 19.5-fold purification by 40-80% ammonium sulfate precipitation and diethyl aminoethyl anion exchange chromatography 14 …”
Section: Resultssupporting
confidence: 63%
“…The desired band size for amylase of 50 KDa was obtained ( Figure 6). Amylase enzymes with same molecular weight was reported in the previous literature [15,16]. These results revealed that Bacillus Subtilis strain identified for amylase production from salt mines of Karak will be a good option for those industrial applications have high pH and temperature as common laboratory conditions.…”
Section: Partial Purification Of Amylasessupporting
confidence: 70%
“…Reducing sugars were quantified by the DNS method by using glucose as a standard (31). One unit of amylase activity was defined as the amount of enzyme that liberated 1 mol of glucose per s. In addition, ␣-amylase activity on soluble potato starch was determined by measuring its iodine-complexing ability according to the protocol described by Giraud et al (12).…”
Section: Methodsmentioning
confidence: 99%